Tailoring the synergistic effect of integrated polypyrrole hydrogel on the adsorption activity of rice husk-based activated carbon (polypyrrole/activated carbon composite) for bisphenol-A and 4-chlorophenol: experimental and theoretical analysis - Farhan, Amna M.; Khaled, Eman S. H.; Abdel-Khalek, Ahmed A.; El-Sherbeeny, Ahmed M.; Al Zoubi, Wail; Abukhadra, Mostafa R. (Frontiers in Bioengineering and Biotechnology, 2025)
Rice husk-derived activated carbon was hybridized with polypyrrole hydrogel (Pyh), producing advanced nanocomposite (Pyh/AC). The composite was applied as an enhanced adsorbent for two forms of toxic phenolic compounds, particularly bisphenol-A (BSP-A) and 4-chlorophenol (4-CL). The adsorption studies were evaluated considering the synthetic effect of Pyh based on the criteria of statistical physics equilibrium modeling. The reported saturation adsorption capacities for BSP-A and 4-CL using Pyh/AC are 321.4 mg/g and 365.8 mg/g, respectively. These values are significantly higher than the estimated values for the hydrogel in separated form. The analysis of the steric properties validated the saturation of the composite with about 169.7 mg/g and 119.5 mg/g as active site density during the uptake of BSP-A and 4-CL, respectively. These values are higher than the estimated densities using Pyh (110.5 mg/g (BSP-A) and 99.3 mg/g (4-CL)), demonstrating the positive impact of the hybridization process in terms of surface area, porosity, and incorporated chemical functional groups. Furthermore, the capacity of each site on the structure of Pyh/AC to accommodate up to 3 molecules of BSP-A and 6 molecules of 4-CL displays the operation of multi-molecular mechanisms and the ordering of these adsorbed molecules vertically and in non-parallel forms. The adsorption energies, either based on classic (<21 kJ/mol) or advanced (<20 kJ/mol) isotherm studies, reflect the physisorption of the phenolic compounds on the surface of Pyh/AC. The composite also shows thermodynamically stable properties and the uptake reactions that occurred with exothermic, favorable, and spontaneous properties.